An intersectional feminist theory of moral responsibility - Ciurria, Michelle (New York, NY : Routledge, 2020)
"This book develops an intersectional feminist approach to moral responsibility. It accomplishes four main goals. First, it outlines a concise list of the main principles of intersectional feminism. Second, it uses these principles to critique prevailing philosophical theories of moral responsibility. Third, it offers an account of moral responsibility that is compatible with the ethos of intersectional feminism. And fourth, it uses intersectional feminist principles to critique culturally normative responsibility practices. This is the first book to provide an explicitly intersectional feminist approach to moral responsibility. After identifying the five principles central to intersectional feminism, the author demonstrates how influential theories of responsibility are incompatible with these principles. She argues that a normative theory of blame should not be preoccupied with the agency or traits of wrongdoers; it should instead underscore, and seek to ameliorate, oppression and adversity as experienced by the marginalized. Apt blame and praise, according to her intersectional feminist account, is both communicative and functionalist. The book concludes with an extensive discussion of culturally-embedded responsibility practices, including asymmetrically-structured conversations and gender- and racially-biased social spaces. An Intersectional Feminist Approach to Moral Responsibility presents a sophisticated and original philosophical account of moral responsibility. It will be of interest to philosophers working at the crossroads of moral responsibility, feminist philosophy, critical race theory, queer theory, critical disability studies, and intersectionality"--
OCLC-licensed vendor bibliographic record.
Keywords: Feminist theory; Responsibility; Feminism -- Moral and ethical aspects; PHILOSOPHY / Ethics & Moral Philosophy